APPLICATION OF ERGONOMICS TO REDUCE RISK FACTORS FOR MUSCULOSKELETAL DISORDERS IN CONSTRUCTION WORKERS (Fiep Bulletin - online, 2012)
This research presents an assessment of ergonomic risk in certain activities performed by workers who work in private construction projects of the Federal Technological University of Paraná, in Curitiba. To this end, it was necessary to use a Nordic questionnaire as a research tool to identify the existence of painful body regions, reported by 42 workers over the past twelve months worked. With the questionnaire application, it was observed that construction workers indicated that the pains occur in more than one body region. Workers interviewed; due to negligence or even lack of knowledge of the correct procedures, may be surprised by aggravating problems in the spinal column, in addition to musculoskeletal disorders and discomfort caused by painful symptoms in the body. The bricklayers, janitors, electricians and plumbers, reported suffering from minor pain, yet uncomfortable. consequently, these professionals reported they were aware of the pains and musculoskeletal injuries, which would be the consequences of using excessive force, incorrect postures and repetitive movements. Thus, it is concluded that there is need for constant training, with better insight into the ergonomic risks to which these workers are exposed while performing their activities, such as manual lifting and carrying weights, repetitive motions, incorrect postures and risks of work-related accidents.
Keywords: ergonomic risks; construction; Nordic Questionnaire